Pulmonary problems and management concerns in youth sports - Orenstein, D. M. (Pediatric Clinics of North America, 2002)
In the overwhelming majority of exercising youngsters, exercise tolerance is limited by cardiovascular and muscular factors, not the lungs. Even at exhaustion, pulmonary reserve is considerable. Yet some young athletes do experience respiratory problems with exercise. These problems can be assigned to several categories, including those related to underlying acute and chronic respiratory conditions (principally respiratory tract infections, asthma, cystic fibrosis, chest wall deformities, and neuromuscular disorders), and apparent but nonpathological problems (the heavy breathing of anaerobic exercise, relative deconditioning, and anxiety). There are also situations that seem to be problematic but need not be (having the diagnosis of asthma or cystic fibrosis). Pharmacologic management of respiratory problems and perceived problems can be difficult and is discussed with the particular disorder.